Forthcoming changes in world population distribution and global connectivity: implications for global foresight. (2018) - Zinkina, Julia; Shulgin, Sergey; Andreev, Alexey; Aleshkovski, Ivan; Korotayev, Andrey
For the first-world citizens, globalisation seems to be an all-pervasive phenomenon. Our research reveals that global connectivity rates differ dramatically for various countries and correspondingly, their populations. What will this picture look like in, say, 50 years? We combine demographic projections with our knowledge on the recent dynamics of national rates of global connectivity to estimate the proportion of world population which is expected to live in countries with varying rates of global connectivity. We show that the distribution of world population among the states with various rates of global connectivity is bound to experience significant changes in the coming decades, which should be taken into account at various attempts of providing global foresight.